2018
DOI: 10.1007/978-3-030-01325-7_21
|View full text |Cite
|
Sign up to set email alerts
|

A Deterministic Distributed 2-Approximation for Weighted Vertex Cover in $$O(\log N\log \varDelta /\log ^2\log \varDelta )$$ Rounds

Abstract: We present a deterministic distributed 2-approximation algorithm for the Minimum Weight Vertex Cover problem in the CONGEST model whose round complexity is O(log n log ∆/ log 2 log ∆). This improves over the currently best known deterministic 2-approximation implied by [KVY94]. Our solution generalizes the (2 + ǫ)-approximation algorithm of [BCS17], improving the dependency on ǫ −1 from linear to logarithmic. In addition, for every ǫ = (log ∆) −c , where c ≥ 1 is a constant, our algorithm computes a (2 + ǫ)-ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…By setting ε = 1/(nW ), we conclude the following result for an f -approximation (recall that we assume that vertex degrees and weights are polynomial in n): Additionally, we get the following range of parameters for which the round complexity is still optimal: For f = O(1) we also get an extension of range of parameters for which the round complexity is optimal. This extension is almost exponential compared to the allowed ε = (log ∆) −O (1) in [BEKS18].…”
Section: Putting It Togethermentioning
confidence: 92%
See 1 more Smart Citation
“…By setting ε = 1/(nW ), we conclude the following result for an f -approximation (recall that we assume that vertex degrees and weights are polynomial in n): Additionally, we get the following range of parameters for which the round complexity is still optimal: For f = O(1) we also get an extension of range of parameters for which the round complexity is optimal. This extension is almost exponential compared to the allowed ε = (log ∆) −O (1) in [BEKS18].…”
Section: Putting It Togethermentioning
confidence: 92%
“…We refer to the additive increase of the dual variable δ(e) as deal(e). Similarly weighted approximation time algorithm to [BEKS18], we use levels to measure the progress made by a vertex. Whenever the level of a vertex increases, it sends a message about it to all incident edges, which multiply (decrease) their deals by 0.5.…”
Section: Tools and Techniquesmentioning
confidence: 99%
“…We note that [16] was the first to achieve this running time with no dependence on W , the maximum weight of the nodes. Recently, Ben-Basat et al [6] showed an O(O PT 2 log O PT ) rounds algorithm for computing the minimal (unweighted) vertex cover and a O(O PT ) rounds for a (2 + ε)-approximation. Here, O PT is the size of the smallest cover and thus these algorithms are adequate when a small solution exists.…”
Section: Related Workmentioning
confidence: 99%
“…A maximal matching can be obtained in O(log ∆ + log 3 log n) rounds by plugging the algorithm of Fischer [Fis17] into the framework of Barenboim, Elkin, Pettie, and Schneider [BEPS16]. For weighted minimum vertex cover, the fastest 2-approximation is an O(log n log ∆/ log 2 log ∆) algorithm by Ben-Basat, Even, Kawarabayashi, and Schwartzman [BEKS18], while for a (2 + ǫ)-approximation only the tight O(log ∆/ log log ∆) rounds are needed, as first shown by Bar-Yehuda, Censor-Hillel, and Schwartzman [BCS17].…”
Section: Bhattacharya Et Al [Bchn18mentioning
confidence: 99%